Modified Lothrop technique to address complicated chronic frontal sinusitis - Araújo, João Pedro (2015)
Introduction: The authors report a complicated chronic frontal sinusitis, resolved with modified Lothrop procedure.Material and Methods: A 39 years old male, had his frontal bone reconstructed after head trauma with fracture of the frontal bone. After this, multiple episodes of recurrent acute frontal sinusitis associated with facial cellulitis emerged. He also had severe headaches due to dehiscence of the posterior wall of the frontal sinus. As there was severe stenosis of the frontal recess he was treated with modified Lothrop procedure.Results: After scarring there was a good epithelization of the frontal cavity, and the inflammatory process resolved.Conclusion: Chronic sinusitis is a known complication of frontal bone fracture. In the presented case the modified Lothrop procedure is a valid and successful choice. Literature review confirms that this is an effective procedure to treat complicated chronic sinusitis, with few complications and good tolerance when compared to alternative surgical techniques.